Investigation of Structural and Optical Properties of ZnO Thin Films Grown on Different Substrates by Mist-CVD Enhanced with Ozone Gas Produced by Corona Discharge Plasma - Ece Kutlu-Narin; Polat Narin; Sefer Bora Lisesivdin; Beyza Sarikavak-Lisesivdin (Advances in Condensed Matter Physics, 2021)
This study focuses on the growth and physical properties of ZnO thin films on different substrates grown by mist-CVD enhanced with ozone (O3) gas produced by corona discharge plasma using O2. Here, O3 is used to eliminate the defects related to oxygen in ZnO thin films. ZnO thin films are grown on amorphous soda-lime glass (SLG) and single crystals SiO2/Si (100) and c-plane Al2O3 substrates at 350°C of low growth temperature. All ZnO thin films show dominant (0002) diffraction peaks from X-ray diffraction (XRD). As expected, full width at half maximum (FWHM) of (0002) is decreasing in ZnO thin films on single-crystal substrates, especially c-Al2O3 due to similar crystal structure. It is found that the strain in the films is lowest in ZnO/c-Al2O3. The surface morphologies of the thin films are studied with atomic force microscopy (AFM) and scanning electron microscopy (SEM) measurements. Grown ZnO films have a hexagonal and triangular nanostructure with different nanostructure sizes depending on the used substrate types. The calculated surface roughness is dramatically decreased in ZnO/c-Al2O3 compared to the other grown structures. The confocal Raman measurements show the E2(H) peak of ZnO thin films at 437 cm−1. It is suggested that O3 gas produced by corona discharge plasma using O2 can be useful to obtain better crystal quality and physical properties in ZnO thin films.